Museums in Action: How Museums are redefining their Role in European Projects - Siri, Anna; Molek, Joanna; Olcese, Gianluca (Journal of Ecohumanism, 2024)
An innovative and detailed analysis of the role of museums in European Union-funded projects is presented in this article, based on a thorough search of the European CORDIS database. The study explores how museums have transformed from being passive custodians of cultural heritage to becoming dynamic and multifunctional actors in European research and innovation. Through a systematic analysis of European projects funded in the 2007-2022 period, the article highlights the growing participation of museums in various EU programs, the varied roles they assume-from beneficiary partners to associate collaborators-and their impact in key areas such as education, research, digitization and technological innovation. This research provides both quantitative and qualitative insights into museums’ involvement in shaping European cultural identity and policy development. The paper is of particular interest to policy makers, museum professionals and cultural heritage researchers, offering a unique perspective on the evolving role of museums in the European context and future opportunities for collaboration and funding.